1991
DOI: 10.1021/jo00015a020
|View full text |Cite
|
Sign up to set email alerts
|

Positional reactivity of dibenzofuran in electrophilic substitutions

Abstract: 95; H, 7.31; N, 10.15.4-Amino-5-tert -butyl-rl'-(dimethylamino)bipheny1-3-carbonitrile (8c) was prepared from 0.17 g (0.49 mmol) of 13 in 25 mL of CH3CN by addition of 1 mL of HBF, (40% in ether).After being stirred for 45 min, the solution was treated with lu until an aqueous extract was no longer acidic. The solvent was evaporated, and the residue was several times extracted with ether. The resulting colorless material was recyrstallized from methanol and yielded 70 mg (51%) of 8c: mp 137-138 "C; MS m / z 29… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 2 publications
0
10
0
Order By: Relevance
“…6a, S10 and S15 †). 52 Borazarophenanthrenes have been shown to pose a particular challenge to many reactivity models, with FMO theory, the condensed Fukui function and atomic charge calculations all failing to predict the observed reactivity patterns (Fig. S15 †).…”
Section: Large-scale Examination Of Substrate Scope Of Ionisation Ene...mentioning
confidence: 99%
“…6a, S10 and S15 †). 52 Borazarophenanthrenes have been shown to pose a particular challenge to many reactivity models, with FMO theory, the condensed Fukui function and atomic charge calculations all failing to predict the observed reactivity patterns (Fig. S15 †).…”
Section: Large-scale Examination Of Substrate Scope Of Ionisation Ene...mentioning
confidence: 99%
“…1, which is known to have a distinct reactivity for acylation/bromination and nitration. 27 The former occurs at the 2-position, whereas the latter occurs at the 3-position. Initially, we coupled the known 17 secondary bromide 3 to diol 4 to give alcohol 5 with high regioselectivity but low yield (5%).…”
Section: Synthesis Of Ndbf-ip3/ammentioning
confidence: 99%
“…Such reactions provide, either mono substituted [5] or multi-substituted dibenzo [b,d]furans [6]. However the disadvantage of such reactions is that we tend to get substitutions at undesired position on the heterocycle.…”
Section: Introductionmentioning
confidence: 99%
“…A literature survey revealed that most of the substituted dibenzo [b,d]furans have been synthesized by electrophilic substitution of commercially available dibenzo [b,d]furan. Such reactions provide, either mono substituted [5] or multi-substituted dibenzo[b,d]furans [6]. However the disadvantage of such reactions is that we tend to get substitutions at undesired position on the heterocycle.…”
Section: Introductionmentioning
confidence: 99%